Expression of Wnt pathway genes in polyps and medusa‐like structures of Ectopleura larynx (Cnidaria: Hydrozoa). Issue 5 (20th September 2013) - Nawrocki, Annalise M.; Cartwright, Paulyn
SUMMARY The canonical Wnt signaling pathway is conserved in its role in axial patterning throughout Metazoa. In some hydrozoans (Phylum Cnidaria), Wnt signaling is implicated in oral–aboral patterning of the different life cycle stages—the planula, polyp and medusa. Unlike most hydrozoans, members of Aplanulata lack a planula larva and the polyp instead develops directly from a brooded or encysted embryo. The Aplanulata species Ectopleura larynx broods such embryos within gonophores. These gonophores are truncated medusae that remain attached to the polyps from which they bud, and retain evolutionary remnants of medusa structures. In E. larynx, gonophores differ between males and females in their degree of medusa truncation, making them an ideal system for examining truncated medusa development. Using next‐generation sequencing, we isolated genes from Wnt signaling pathways and examined their expression in E. larynx. Our data are consistent with the Wnt pathway being involved in axial patterning of the polyp and truncated medusa. Changes in the spatial expression of Wnt pathway genes are correlated with the development of different oral structures in male and female gonophores. The absence of expression of components of the Wnt pathway and presence of a Wnt pathway antagonist SFRP in the developing anterior end of the gonophore suggest that downregulation of the Wnt pathway could play a role in medusa reduction in E. larynx.